KEDUDUKAN ORGAN PERSEROAN DALAM PERSEROAN TERBATAS PERORANGAN KRITERIA UMK - Kusuma, Ida Bagus Adhi Perdana; Wiryawan, I Wayan (Kertha Desa; Vol 11 No 1 (2023), 2023)
Tujuan penulisan untuk menambah pengetahuan pendirian perseroan terbatas perorangan kriteria UMK dan mengetahui kedudukan organ perseroan terbatas perorangan kriteria UMK. Penulisan ini menggunakan metode penelitian hukum normatif dengan mengkaji peraturan terkait perseroan terbatas perseorangan, dengan menerapkan pendekatan perundang- undangan dan pendekatan konseptual, mengkaji bahan hukum primer, sekunder serta tersier kemudian hasilnya dijabarkan secara deskriptif. Hasil penelitian ditunjukkan bahwa Pe ndirian suatu pe rseroan perorangan yaitu dapat didirikan oleh seorang Warga Negara Indonesia, dengan Pernyataan Pendirian dalam bahasa Indonesia. Kemudian perseroan perorangan tersebut didaftarkan kepada Menteri Hukum dan HAM untuk mendapatkan sertifikat pendaftaran secara online sehingga memperolah status badan hukum.   Kedudukan organ perseroan PT terdiri atas RUPS, Direksi dan Dewan Komisaris sebagaimana diatur dalam Pasal 109 angkat (1) UU Cipta Kerja, sedangkan organ Perseroan Perorangan hanya terdiri dari Pemegang Saham sekaligus Direktur, serta tanpa adanya organ Dewan Komisaris sebagaimana diatur secara eksplisit pada ketentuan pasal 7 dan pasal 8 ayat (4) huruf g PP No. 8/2021. Kata Kunci: Perseroan Terbatas, Perseroan Perorangan, Organ Perseroan. The purpose of writing is to increase knowledge of the establishment of an individual limited liability company with the UMK criteria and find out the position of the organs ofan individual limited liability company with the UMK criteria. This writing uses normative legal research methods by reviewing regulations related to individual limited liability companies, by applying statutory approaches, and conceptual approaches, and using primary, secondary and tertiary legal materials then the results are described descriptively. The results of the study show that the establishmnt of anindividual company can be established by 1 (one) person or an Indonesian citizen, with a statement of establishment in the Indonesian language. Then the individual company is registered with the Minister and obtains an online registration to get certificate so that it obtains the status of a legal entity. The position of PT company organs consists of GMS, Directors and Board of Commissioners as stipulated in Article 1 point (2) of the Company Law in conjunction with Article 109 point (1) of the Job Creation Law, while the organs of an Individual Company only consist of Shareholders as well asDirectors, and there is no Board organ. Commissioners as explicitly stipulated in the provisions of 7 paragraph (2) letter g and article 8 paragraph (4) letter g PP No. 8/2021. Keywords: Limited Liability Company, Individual Company, Company Organs.